2015
DOI: 10.1111/ijd.12854
|View full text |Cite
|
Sign up to set email alerts
|

Remitting seronegative symmetrical synovitis with pitting edema associated with parvovirus B19 infection: two new cases and review of the comorbidities

Abstract: We want to underline the importance for patients with RS3PE to be seen by dermatologists who should become familiar with this syndrome and remark that Parvovirus B19 infection may be a potential cause of RS3PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…The hypothesis has long been considered that in a genetically predisposed patient, an environmental factor, possibly a virus, may induce monocyte and dendritic cell activation and the production of pro-inflammatory cytokines that induce manifestations characteristic of PMR (21,22). However, although several infectious agents have been investigated as possible triggers, the results are inconclusive.…”
Section: N Infectious Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis has long been considered that in a genetically predisposed patient, an environmental factor, possibly a virus, may induce monocyte and dendritic cell activation and the production of pro-inflammatory cytokines that induce manifestations characteristic of PMR (21,22). However, although several infectious agents have been investigated as possible triggers, the results are inconclusive.…”
Section: N Infectious Agentsmentioning
confidence: 99%
“…Cimmino et al demonstrated that antibodies to adenovirus (ADV) and respiratory syncytial virus (RSV) were significantly more prevalent in PMR patients, suggesting that ADV and RSV might be the possible microorganisms responsible for triggering PMR in elderly people (24). Although a few studies reported the presence of an association between parvovirus B19 and PMR, the results have been not replicated in larger studies (21,25). Finally, no role of current or previous hepatitis B virus infection has been demonstrated in the pathogenesis of the majority of cases of polymyalgia rheumatic (26).…”
Section: N Infectious Agentsmentioning
confidence: 99%
“…The most typical is the papular purpuric 'gloves and socks' syndrome , but atypical exanthems, have been reported and may pose a diagnostic challenge. So far, systemic contributes dealing with atypical exanthems in the course of B19V infection are very limited whereas single case reports have been more frequently described . In our series of 390 consecutive patients with atypical exanthems, including 120 children and 270 adults, B19 V infection was found in approximately 5% of cases, both in children and adults.…”
Section: Discussionmentioning
confidence: 70%
“…No other cause for RS3PE has been found and the authors suggested an etiological relationship between RS3PE and Parvovirus B19 infection 24 . Similarly, Drago et al described another two cases who had RS3PE syndrome associated with Parvovirus B19 infection 25 . In general no clear association was reported between an infectious agent and RS3PE.…”
Section: Etiopathogenesismentioning
confidence: 86%